Digital communication of police officers during the Covid-19 pandemic (Vallis Aurea, 2023)
This qualitative study aims to determine which digital communication channels and for what purposes were used by police in rural and suburban parts of Croatia during the COVID-19 pandemic and the obstacles they encountered in doing so. The purpose of the research is a scientific contribution to communication and police sciences, given the lack of such research not only in Croatia but internationally. The practical purpose is the identification of possibilities and limitations of digital communication in policing and aspects of police communication that are important during crises. The semi-structured interview was used in four focus groups of 10 research participants. The results show that during the COVID-19 pandemic, at the request of citizens, police officers often resorted to communication via social media, even though such a method of police communication was not defined as official at the time and despite other serious obstacles such as insufficient technological infrastructure and lack of access to the Internet. The need to create precise work guidelines was identified to avoid problems and prevent citizens’ resistance towards introducing such novelties. This research also points to establishing guidelines and communication protocols between public services to avoid confusion and misinformation.